2015
DOI: 10.1134/s0006297915090023
|View full text |Cite
|
Sign up to set email alerts
|

Chitin and products of its hydrolysis in Vibrio cholerae ecology

Abstract: The role of chitin and its hydrolysis products generated by Vibrio cholerae chitinases in mechanisms of its adaptation in water environments, metabolism, preservation, acquisition of pathogenic potential, and its epidemiological value are reviewed. Chitin utilization by V. cholerae as a source of energy, carbon, and nitrogen is described. Chitin association promotes biofilm formation on natural chitinous surfaces, increasing V. cholerae resistance to adverse factors in ecological niches: the human body and wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 55 publications
0
11
0
Order By: Relevance
“…The results of this study are in accordance with research conducted by Vengadesh et al (2012) found shrimp, shellfish, fish, and squid sold in wet market and supermarket in Malaysia contaminated with V. cholerae. In this study, the cholerae can use chitin as a source of energy, carbon, and nitrogen (Markov et al, 2015). In the aquatic environment, chitin will be colonized by the chitinolytic bacteria (Gooday et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study are in accordance with research conducted by Vengadesh et al (2012) found shrimp, shellfish, fish, and squid sold in wet market and supermarket in Malaysia contaminated with V. cholerae. In this study, the cholerae can use chitin as a source of energy, carbon, and nitrogen (Markov et al, 2015). In the aquatic environment, chitin will be colonized by the chitinolytic bacteria (Gooday et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Chitinases have been received much attention and were believed to play a central role in the chitin degrading processes by bacteria [ 13 ]. Many physiological characteristics of vibrios were associated with the capacity of chitin-degradation, including chemotaxis, cell division, biofilm formation and natural competence [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Other tick researchers have speculated that the breakdown of the peritrophic matrix, a semipermeable membrane that surrounds the tick blood meal, contributes to the availability of nutrients for residing pathogens [31,32]. Because the tick peritrophic matrix is composed of chitin [71], bacteria able to degrade this N-acetylglucosamine polymer may be able to generate carbon as an energy source [34,72]. Given that Dv and Aa ticks molted between weeks 4 and 6, chitin may have been available preceding the molt (between weeks 2 and 4), which may explain the 11-fold Ft replication in Dv ticks and 5-fold Ft replication in Aa ticks between weeks 2 and 4.…”
Section: Discussionmentioning
confidence: 99%
“…As such, it has been speculated that chitin may be used as an energy source by tick-borne bacterial pathogens [31][32][33]. Chitin cleavage can be performed by chitinases and bacterial chitinases have been shown to promote bacterial persistence in marine environments and mammals [34][35][36][37]. We searched the Ft LVS genome for putative chitinases and, using a conserved domain search, found that gene locus FTL1793 (annotated as a hypothetical protein) contains a region encoding a putative glycosyl hydrolase (GH) 18 chitinase Dlike region ( Figure S5A).…”
Section: Ftl1793 Exhibits Chitinase Activitymentioning
confidence: 99%